Faktor-Faktor Yang Memengaruhi Motivasi Petani Padi Dalam Penggunaan Agensia Pengendali Hayati - Budianto, Taufik; Ismarlin, Ina Fitria; Astuti, Siti (Jurnal Pertanian Khairun, 2025)
The use of biological control agents (BCA) in rice cultivation is an environmentally friendly alternative strategy for pest control, yet its adoption rate among farmers remains low. This study aims to assess the level of farmer motivation in using BCA and to analyze the influencing factors. The research was conducted in Temuwuh Village, Dlingo Subdistrict, Bantul Regency, using a quantitative approach through a survey method involving 80 rice farmers selected via proportional random sampling. Data were analyzed using multiple linear regression. The results indicate that the role of agricultural extension workers and farmer groups has a significant effect on farmers' motivation, whereas non-formal education, farming experience, land area, and government support do not show significant influence. The adjusted R square value of 0.436 indicates that 43.6% of the variation in farmers’ motivation is explained by the variables in the model. These findings highlight the importance of institutional approaches, particularly through the role of extension workers and farmer groups, in shaping farmers’ motivation to adopt biological control agents. It is recommended that agricultural assistance programs enhance the function of farmer groups and the field presence of extension workers to increase the adoption of environmentally friendly agricultural technologies.